Calculated images of dislocations in crystals on section topograms - Novіkov, S.M.; Fodchuk, І.M.; Fedortsov, D.G.; Struk, A.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
By means of numerical solution of the Takagi equations, modeling of X-ray topographic images of deformation fields of the dislocation loops and dislocation of different types. Diffraction images created by dislocations and dislocation loops of different size and spatial location are complicated and versatile in their thin structure.